2017
DOI: 10.1002/ecs2.1732
|View full text |Cite
|
Sign up to set email alerts
|

Tree species diversity and identity effects on soil properties in the Huoditang area of the Qinling Mountains, China

Abstract: Citation: Zheng, X., X. Wei, and S. Zhang. 2017. Tree species diversity and identity effects on soil properties in the Huoditang area of the Qinling Mountains, China. Ecosphere 8(3):e01732. 10.1002/ecs2.1732Abstract. Soil properties, such as carbon stock, nitrogen stock, cation exchange capacity (CEC), bulk density (BD), and pH, may have a different status when the forest type changes. We were interested in how tree species identity and diversity affect soil properties. Forest soil profiles were sampled at a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 42 publications
2
16
1
Order By: Relevance
“…Temperature may enhance the soil microbial process and soil biochemical processes, such as denitrification, which are positively related to temperature [21]. Tree species can have a strong influence on soil properties [22]. Different vegetation types can have varying influence on the rate of soil N and P input, and these can affect the soil nutrient accumulation and loss [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Temperature may enhance the soil microbial process and soil biochemical processes, such as denitrification, which are positively related to temperature [21]. Tree species can have a strong influence on soil properties [22]. Different vegetation types can have varying influence on the rate of soil N and P input, and these can affect the soil nutrient accumulation and loss [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, because of the overlapping nature of belowground networks (e.g., mycelium and fine roots) and aboveground canopies in natural forests, the soil fungal communities around tree trunks may also be influenced by the fine roots and fallen leaves from other adjacent plants. Likewise, several studies have reported that tree species identity can affect a series of soil properties in local forests, such as pH, element content and physical structure [93,94]. In turn, plant-mediated variance in soil properties has been inferred to affect soil fungal communities directly [28], which reflected the interactive effects of biotic and abiotic variables on fungal communities [95].…”
Section: Biogeographic Pattern Of Forest Soil Mycobiome and Its Possimentioning
confidence: 99%
“…Liu et al (2020) found the main vegetation types used in ecological restorations have different behaviors in reducing runoff and sediment yield, for example, grassland showed a higher performance in maintaining runoff yield and reducing sediment delivery compared to forestland and scrubland. Plant diversity can affect soil erosion and runoff by changing the pattern of vertical vegetation (Martin et al, 2010;Gómez et al, 2018), enhancing the light use efficiency of aboveground vegetation cover (Onoda et al, 2014) and increasing the diversity of the litter layer and root density (Zheng et al, 2017;. The effects of the vegetation structure on rainfall include the aboveground layer, surface litter layer and belowground root layer.…”
Section: Mechanism Of Vegetation Effects On Soil and Nutrient Exportmentioning
confidence: 99%